Kedaulatan Negara Indonesia Ditinjau dari Sisi Politik Hukum Pertahanan Negara - Rasona Sunara Akbar; Kiki Ananda Mustari; Dio Nasa R; Feryan Wahyu; Kamal Fadhel; Gabriel David; Ramadhani Ikhsan (Departement of Mathematics Education, 2024)
National defense is a crucial aspect in maintaining the sovereignty, integrity and security of a country. This discussion reviews various aspects related to national defense, from concept to implementation in law and policy in Indonesia. The research method used is normative analysis of various legal documents and expert views related to national defense. The results of the discussion highlight the importance of integrating military and non-military defense in facing various developing threats. Inter-agency coordination, including through the National Defense Council, is considered crucial in formulating effective defense policies and strategies. In a political context, national defense is seen as the result of the political process and public policy. However, there is also the concept of legal politics which is the basis for determining the laws that apply in a country. In conclusion, national defense requires clear and structured regulations and the involvement of all elements of society to maintain stability and sustainability of defense. Continuous evaluation of the country's defense system is necessary to face the dynamics of ever-growing threats. National defense is an implementation of social contract theory which involves an agreement between citizens in society to protect their rights and obligations and ensure the harmony of interests. Every citizen has the right and obligation to participate in efforts to defend the country, both physically and non-physically, in accordance with the provisions of applicable law. Awareness of the importance of national defense, especially among the younger generation, needs to be increased to ensure their role in advancing the nation is optimal